2017
DOI: 10.1038/s41598-017-00668-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four kinds of electromagnetic fields (EMF) with different frequency spectrum bands on ovariectomized osteoporosis in mice

Abstract: Electromagnetic fields (EMF) was considered as a non-invasive modality for treatment of osteoporosis while the effects were diverse with EMF parameters in time domain. In present study, we extended analysis of EMF characteristics from time domain to frequency domain, aiming to investigate effects of four kinds of EMF (LP (1–100 Hz), BP (100–3,000 Hz), HP (3,000–50,000 Hz) and AP (1–50,000 Hz)) on ovariectomized (OVX) osteoporosis (OP) in mice. Forty-eight 3-month-old female BALB/c mice were equally assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…He et al suggest that ELF-PEMF suppressive effects are mediated by endocrine effects of osteoblasts [67], a hypothesis supported by several other studies [61,[69][70][71][72]. While Wang et al proposed that regulation of osteoclastogenesis is strongly dependent on the intensity of the applied ELF-PEMF [73], Lei et al showed bone metabolic ELF-PEMF effects in osteoporotic (ovariectomized) mice which strongly depended on the frequency range applied [74]. While lower frequencies induced osteoblast function, higher frequencies inhibited osteoclast function [74].…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 93%
See 1 more Smart Citation
“…He et al suggest that ELF-PEMF suppressive effects are mediated by endocrine effects of osteoblasts [67], a hypothesis supported by several other studies [61,[69][70][71][72]. While Wang et al proposed that regulation of osteoclastogenesis is strongly dependent on the intensity of the applied ELF-PEMF [73], Lei et al showed bone metabolic ELF-PEMF effects in osteoporotic (ovariectomized) mice which strongly depended on the frequency range applied [74]. While lower frequencies induced osteoblast function, higher frequencies inhibited osteoclast function [74].…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 93%
“…While Wang et al proposed that regulation of osteoclastogenesis is strongly dependent on the intensity of the applied ELF-PEMF [73], Lei et al showed bone metabolic ELF-PEMF effects in osteoporotic (ovariectomized) mice which strongly depended on the frequency range applied [74]. While lower frequencies induced osteoblast function, higher frequencies inhibited osteoclast function [74]. This is in line with our previous work, showing that the ELF-PEMF with a frequency of f = 16 Hz, which most effectively induced osteoblast function, did not affect osteoclast function [32].…”
Section: Elf-pemf Effects On Bone Cell Functionmentioning
confidence: 99%
“…Different types and parameters of magnetic fields may have different effects on bone cells, some of which are summarized in Table 4. Irrespective of whether SMFs or PEMFs are employed, the effects on bone regeneration may be related mainly to activation of Wnt/β-catenin (Zhou et al, 2012), RANK/RANKL/OPG (Lei et al, 2017(Lei et al, , 2018 or MAPK (mitogen-activated protein kinase) (Yong et al, 2016) signaling pathways. Moreover, bone tissue may be sensitive to low-frequency PEMFs, which may be associated with strong transmembrane potential changes and Ca 2+ influx.…”
Section: Biological Effects and Mechanisms Of Magnetic Materials On Bmentioning
confidence: 99%
“…A vast range of frequencies, intensities, durations of exposure, pulses [Markov, ; Liu et al, ; Li et al, ; Lei et al, ], or even waveforms [Zhou et al, ] have been investigated and no consensus has been thus far reached. The studies herein include investigated frequencies ranging from 0.2 to 1 kHz, with signals often composed of bursts or trains of pulses of different duration and frequency (up to 27.1 MHz) and with intensities of up to 1 T, and the range of tested parameters sometimes appears to be more strongly motivated by the constraints of the equipment used in the studies than scientific evidence.…”
Section: Therapeutic Effects Of Emfs On Bonementioning
confidence: 99%